The effect of polarization charges on energy of univalent and bivalent donors in a spherical quantum dot - Boichuk, V.I.; Bilynskyi, I.V.; Leshko, R.Ya. (Condensed Matter Physics, 2008)
The energy of electrons of univalent and bivalent impurity of a spherical β -HgS/CdS nanoheterostructure is calculated as a function of quantum dot radius by the variation technique in the case of finite and infinite wells in the effective mass approximation. The effect of polarization charges which arise at the separation boundary of the media is studied taking into account both the existence and the absence of an intermediate layer, where dielectric permittivity depends on the coordinate.